Calibrating microfluidic pressure correction functions in Laval nozzle flow by eliminating production accuracy influences. Issue 1 (October 2016) - Groll, Rodion; Gomez, Juan
Abstract: The investigated case is a micronozzle flow with Knudsen numbers in the slip‐flow regime near the nozzle throat in vacuum environment. Compared gases are neon, argon, krypton and xenon. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)